Mapping Trend of Artificial Intelligence (AI) in Green Jobs Through Bibliometrics Analysis - Razzan Adrian Wowiling, Fatih (UIN Sunan Gunung Djati Bandung, 2025)
The entire world is becoming increasingly concerned about the rising birth rates and the uncontrolled growth of industry, which is becoming more detached from norms and ethics day by day. This is further exacerbated by the emergence of AI technology, which has triggered public fear over job scarcity, potentially leading to a loss of public awareness regarding the importance of maintaining environmental integrity and sustainability in the pursuit of livelihood. At the same time, the United Nations’ Sustainable Development Goals (SDGs) have become a trending framework for regulating industrial growth in the era of Society 5.0, in which green jobs are seen as a hopeful solution to the ongoing dilemma. Given these conditions, this study aims to analyze whether the trend of AI usage in various aspects of life can serve as a bridge to achieving the SDGs, particularly in environmental sustainability through green jobs. This study employs a qualitative approach, utilizing bibliometric analysis based on data from the past decade (2015–2025) via the VOSviewer software. A total of 421 research publications is retrieved from Scopus using the keywords